Long-Term Care Insurance: Knowledge Barriers, Risk Perception and Adverse Selection - Martin Boyer; Philippe De Donder; Claude Fluet; Marie-Louise Leroux; Pierre-Carl Michaud (Center for Economic Studies and ifo Institute (CESifo), 2017)
We conduct a stated-choice experiment where respondents are asked to rate various insurance products aimed to protect against financial risks associated with long-term care needs. Using exogenous variation in prices from the survey design, and objective risks computed from a dynamic microsimulation model, these stated-choice probabilities are used to predict market equilibrium for long-term care insurance using the framework developped by Einav et al. (2010). We investigate in turn causes for the low observed take-up of long-term care insurance in Canada despite substantial residual out-of-pocket financial risk. We first find that awareness and knowledge of the product is low in the population: 44% of respondents who do not have long-term care insurance were never offered this type of insurance while overall 31% report no knowledge of the product. Although we find evidence of adverse selection, results suggest it plays a minimal role in limiting take-up. On the demand side, once respondents have been made aware of the risks, we find that demand remains low, in part because of misperceptions of risk, lack of bequest motive and home ownership which may act as a substitute.
Keywords: I11; 330; long-term care insurance; adverse selection; stated-preference; health; insurance